2021
DOI: 10.3389/fenrg.2021.696213
|View full text |Cite
|
Sign up to set email alerts
|

Phase Change Material of Copper–Germanium Alloy as Solar Latent Heat Storage at High Temperatures

Abstract: A copper–germanium alloy (Cu–Ge alloy) was examined as a phase change material, at temperatures exceeding 600°C, for latent heat storage in solar thermal applications. First, the thermo-physical properties of the Cu–Ge alloy were examined using differential scanning calorimetry, thermomechanical analysis, and laser flash analysis. Second, to evaluate the thermal response and reliability of the Cu–Ge alloy, the cyclic properties of thermal charge/discharge were examined under various thermal conditions. The all… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 38 publications
0
2
0
Order By: Relevance
“…As shown in Fig. 9, peaks corresponding to Cu-Ge alloy were clearly observed in the patterns of films annealed at 400-500 °C [17], [18]. Previous studies have shown that annealing treatments at 400 °C are sufficient to induce complete crystallization of Cu3Ge films [19], [20], [21], [22], where the Cu 3 Ge stoichiometric compound is generated as a result of annealing-induced interdiffusion of Cu and Ge atoms.…”
Section: Resultsmentioning
confidence: 75%
“…As shown in Fig. 9, peaks corresponding to Cu-Ge alloy were clearly observed in the patterns of films annealed at 400-500 °C [17], [18]. Previous studies have shown that annealing treatments at 400 °C are sufficient to induce complete crystallization of Cu3Ge films [19], [20], [21], [22], where the Cu 3 Ge stoichiometric compound is generated as a result of annealing-induced interdiffusion of Cu and Ge atoms.…”
Section: Resultsmentioning
confidence: 75%
“…Metallic PCMs have been recently regarded as suitable alternatives owing to their low cost and high melting point . Among these metallic materials, copper (Cu) is regarded as one of the most promising PCMs for high-temperature thermal storage because of its ultra-high melting point (>1000 °C), high thermal conductivity (398 W/m K), and high latent heat (208.7 kJ/kg) . However, if the molten liquid metal is directly used in a TES system, it may cause a crucial corrosion problem especially in the high-temperature operation system, resulting in the increase in the cost of corrosion protection equipment, the liquid leakage, and the reduction of system lifetime. , …”
Section: Introductionmentioning
confidence: 99%
“…Intermetallic compounds are typically ordered solids composed of two or more metals or semimetals, and the properties observed are often superior to the individual constituents. , For the case of silicon and germanium, a large number of binary intermetallic phases are known to exhibit large structural variety including simple close-packed arrangements, polyanionic Zintl phases, and more complex extended clathrate and open-framework networks hosting guest atoms. , This structural variety yields diverse physical properties that are important for a broad range of applications including catalysis, solar-thermal applications, thermoelectrics, , and superconductors . While overarching principles that govern structural arrangements, stabilities, and physical properties are still being developed, the discovery of novel intermetallic compounds can facilitate a broader understanding of complex bonding interactions and open new possibilities for applications. , …”
mentioning
confidence: 99%